Pengaruh Aplikasi Baca Online terhadap Minat Baca Digital Mahasiswa Pendidikan Luar Sekolah Universitas Nusa Cendana - Rosvita Eka Kurniati; Abdul Syukur; Rongky Yakobus Famdale; Samrid Neonufa; Ari Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of digital technology has transformed reading patterns from printed media to digital media. As digital natives, university students tend to utilize online reading applications as sources of information and reading materials. This study aimed to determine the effect of online reading applications on the digital reading interest of students in the Non-Formal Education Study Program at Universitas Nusa Cendana. The study employed an associative quantitative approach with a population of 229 active students from semesters 2 to 8 and a sample of 70 respondents selected using the Slovin formula. Data were collected through a Likert-scale questionnaire distributed via Google Forms and analyzed using simple linear regression. The results showed that online reading applications have a positive and significant effect on students’ digital reading interest, with a significance value of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected. The regression equation obtained was Y=20.034+0.716X. The regression coefficient value of 0.716 indicates that every one-unit increase in the use of online reading applications increases students’ digital reading interest by 0.716 units. Furthermore, the coefficient of determination (R²) value of 0.667 indicates that online reading applications contribute 66.7% to students’ digital reading interest, while the remaining 33.3% is influenced by other factors outside the scope of this study. These findings suggest that online reading applications play an important role in enhancing students’ digital reading interest and supporting self-directed learning in the digital era.